Distinct effects of climate warming on populations of silver fir (Abies alba) across Europe. (11th April 2015) - Gazol, Antonio; Camarero, J. Julio; Gutiérrez, Emilia; Popa, Ionel; Andreu‐Hayles, Laia; Motta, Renzo; Nola, Paola; Ribas, Montserrat; Sangüesa‐Barreda, Gabriel; Urbinati, Carlo; Carrer, Marco; Vetaas, Ole
Abstract Aim Climate change is expected to modify growth trends of forests around the world. However, this modification may vary in strength and intensity across a species' biogeographical range. Here, we study European populations of silver fir (Abies alba) across its southern distribution limits in Spain, Italy and Romania. We hypothesized that growth trends of silver fir will differ across its distribution range, with a marked decline in growth in drought‐prone regions near the species' southernmost biogeographical limits. Location Europe (Spain, Italy, Romania). Methods We collected tree‐ring data from at least 1300 silver fir trees located in 111 sites. The dataset was used to assess and model growth trends, quantified as changes in basal area increment, and to determine how growth responds to climate. Results We found contrasting patterns of basal area increments among countries and sites. Populations of silver fir located outside the Mediterranean area (e.g. northern Italy, Romania) have shown a clear increase in growth over the last two decades, whereas most populations in Spain and southern Italy have displayed a marked decline in growth since the 1980s. The growth of silver fir forests at the south‐western distribution limit is severely constrained by low spring–summer water availability, whereas growth of silver fir forests in non‐Mediterranean areas is limited by cold conditions in late winter to early spring. Main conclusions Climate warming is distinctly modifying growth patterns and responses to climate in silver fir across most of the species' European distribution area. In south‐western Europe the reduction in growth of many populations is related to an observed increase in aridity, whereas in more temperate areas warming is enhancing growth. Our results confirm a decline in the growth of silver fir at its south‐western distribution limits as a consequence of climate warming.